Visceral leishmaniasis in Brazil: revisiting paradigms of epidemiology and control - Dantas-Torres, Filipe; Brandão-Filho, Sinval Pinto (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
In the last 20 years, despite the known underestimation of cases, Brazil registered a marked increase in the incidence of visceral leishmaniasis. The main goal of this review is to reflect on some aspects of this zoonosis in Brazil and also to encourage the discussion in order to find more viable, effective and affordable strategies to be implemented by the Brazilian Leishmaniasis Control Program. The current situation of visceral leishmaniasis in Brazil might be seen as a paradox: the most important aspects of the disease are known, but so far the control of this disease has not yet been achieved. The current control strategies have not been able to prevent the geographical expansion, and even a rise in the incidence and lethality of visceral leishmaniasis. There is a need not only for a better definition of priority areas, but also for the implementation of a fieldwork monitoring system to the disease surveillance that could permit a further evaluation of the control program in areas where visceral leishmaniasis is endemic.